Job-Order Costing dan Penerapannya pada Pekerjaan Interior Hunian Vertikal - Widyo Nugroho; Ayu Fatimah; Arya Javas (Prokons: Jurnal Teknik Sipil, 2021)
Abstract Cost management analysis is one of the decision-making tools related to business management. Making such decisions has direct implications for designing a product costing system, which accumulates the costs of the production process. The most common types of product costing systems are job-order costing and process costing, and a combination of the two, namely operation costing. For work with custom products such as interior work, the job-order costing system is a more appropriate approach when compared to the other two systems. This article examines the literature related to job order costing and its various applications in the industrial world. Then the compilers carried out a study in the application of job-order costing to interior vertical residential work with two types of orders for compiling the cost of goods manufactured. This analysis will assist the developer in determining the sales value per apartment unit where interior work is one of the components in the apartment property value chain. Besides, the cost of goods manufactured is also a guide in controlling production costs and measuring company profitability. In this study, overhead is determined by the normal cost of the previous production year, while direct material and direct labor costs are determined by the standard costs obtained from the unit price survey. From the analysis, it was found that the greater the volume of work, the lower the percentage of overhead costs. On the other hand, the percentage of direct material costs and direct labor will increase variable. Concerning company profitability, orders for the two-bedroom type have higher profitability when compared to orders for the studio type. Keywords: Job-order costing, Interior work, Product costing systems